Immune activation from M. tuberculosis screening tests predicts mortality - Benjamin Seligman; David A. Ganz; Matthew Bidwell Goetz; David O. Beenhouwer (GeroScience, 2026)
Impaired immune responses are a key feature of aging; however, there are few laboratory tests that link these responses to clinical outcomes. Interferon-gamma release assays (IGRAs) for tuberculosis screening quantify release of interferon-gamma by T-cells, and the difference between unstimulated and mitogen-stimulated T-cells is assessed for test validity. We assess this measure’s relationship with all-cause mortality. We obtained the most recent negative and indeterminate outpatient IGRAs from a large health system along with demographics, frailty, lymphocyte count, and inflammatory markers. We removed individuals on hemodialysis or immunosuppressive medications. We assessed the association of mitogen-nil with mortality at 6 months, 1 year, and 5 years by Kaplan-Meier analysis and Cox regression. Among 16,104 individuals, reported mitogen-nil ranged from < 0.01 to ≥ 10 IU/mL, and median (IQR) age was 64 (57, 72). Cumulative mortality (95% CI) at 5 years was estimated at 28% (23%–33%) for values 0–1 versus 19% (18%–19%) ≥ 10. In Cox regression, relative to values ≥ 10, values from 0–1 had hazard ratios for mortality at 6 months, 1 year, and 5 years of 2.77 (1.47–5.22), 2.22 (1.41–3.50), and 1.76 (1.31–2.36). Among those with data, adding lymphocyte count did not alter associations. Lower T-cell response to mitogen stimulation in IGRAs is associated with greater mortality. This common test may provide additional information to risk-stratify patients and as a phenotype of impaired immune response.

The way forward for assessing the human health safety of cosmetics in the EU: Proceedings of Workshop 2 - Vera Rogiers; Emilio Benfenati; Ulrike Bernauer; Laurent Bodin; Patience Browne; Nicolas Cabaton; Qasim Chaudhry; Pieter Jan Coenraads; Emanuela Corsini; Matthew Dent; Corie Ellison; Janine Ezendam; et al. (Archives of Toxicology, 2026)

Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Amendment effectiveness and seasonal variations in a lead contaminated acidic wetland - Matthew R. Noerpel; Anna M. Wade; Aaron R. Betts; Jennifer Goetz; Robert Ford; Amy Krause; Michael Zeolla; Diana Cutt; Stephanie M. Wilson; Todd P. Luxton (Applied Geochemistry, 2025)

Mobilization of porewater Pb and Zn in response to seasonal wetting and drying within contaminated floodplains - Anna M. Wade; Chris S. Eckley; Matthew Noerpel; Jennifer Goetz; David Leptich; Kim Prestbo; David Van de Riet; Steve Sluka; Richard Wilkin; Todd P. Luxton (Science of The Total Environment, 2025)

Correction: Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)

Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)
Female Weddell seals ( Leptonychotes weddellii ) display a mixed capital-income breeding strategy, losing up to 40% of their body mass between birthing and weaning their pups. How and when they regain energy stores, however, remains to be fully explored. To better understand the foraging by lactating Weddell seals, we fitted time-depth recorders and head-mounted cameras on 26 seals in Erebus Bay, Ross Sea, for ~ 5 days in November and December 2018 and 2019. We aimed to (1) identify prey species and foraging depth and (2) investigate relationships between seal physiology and demographics and probability of foraging. We recorded 2782 dives, 903 of which were > 50 m, maximum depth was 449.3 m and maximum duration was 31.1 min. Pup age likely contributes to the probability of a lactating Weddell seal foraging (Est. = 1.21 (SD = 0.61), z = 1.97, p = 0.0484). Among 846 prey encounters, the most frequent prey items were crustaceans (46.2%) and Antarctic silverfish ( Pleuragramma antarcticum , 19.0%); two encounters were observed with juvenile Antarctic toothfish ( Dissostichus mawsoni , 0.2%). We identified substantial variability in foraging behaviour, individually and between locations, and found that lactating seals target many species and some may specialise on certain prey groups.

First observations of Weddell seals foraging in sponges in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Matthew H. Pinkerton; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Jay Rotella; Luisa Federwisch; Daniel P. Costa; Michelle A. LaRue (Polar Biology, 2023)
Attaching cameras to marine mammals allows for first-hand observation of underwater behaviours that may otherwise go unseen. While studying the foraging behaviour of 26 lactating Weddell seals ( Leptonychotes weddellii ) in Erebus Bay during the austral spring of 2018 and 2019, we witnessed three adults and one pup investigating the cavities of Rossellidae glass sponges, with one seal visibly chewing when she removed her head from the sponge. To our knowledge, this is the first report of such behaviour. While the prey item was not identifiable, some Trematomus fish (a known Weddell seal prey) use glass sponges for shelter and in which to lay their eggs. Three of the four sponge foraging observations occurred around 13:00 (NZDT). Two of the three sponge foraging adults had higher-than-average reproductive rates, and the greatest number of previous pups of any seal in our study population, each having ten pups in 12 years. This is far higher than the study population average of three previous pups (± 2.6 SD). This novel foraging strategy may have evolved in response to changes in prey availability, and could offer an evolutionary advantage to some individuals that exploit prey resources that others may not. Our observations offer new insight into the foraging behaviours of one of the world’s most studied marine mammals. Further research on the social aspects of Weddell seal behaviour may increase our understanding of the extent and mechanisms of behavioural transfer between conspecifics. Research into the specific foraging behaviour of especially successful or experienced breeders is also warranted.

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Regional Variation in Winter Foraging Strategies by Weddell Seals in Eastern Antarctica and the Ross Sea - Rob Harcourt; Mark A. Hindell; Clive R. McMahon; Kimberly T. Goetz; Jean-Benoit Charrassin; Karine Heerah; Rachel Holser; Ian D. Jonsen; Michelle R. Shero; Xavier Hoenner; Rose Foster; Baukje Lenting; et al. (Frontiers in Marine Science, 2021)
The relative importance of intrinsic and extrinsic determinants of animal foraging is often difficult to quantify. The most southerly breeding mammal, the Weddell seal, remains in the Antarctic pack-ice year-round. We compared Weddell seals tagged at three geographically and hydrographically distinct locations in East Antarctica (Prydz Bay, Terre Adélie , and the Ross Sea) to quantify the role of individual variability and habitat structure in winter foraging behaviour. Most Weddell seals remained in relatively small areas close to the coast throughout the winter, but some dispersed widely. Individual utilisation distributions ( UDi , a measure of the total area used by an individual seal) ranged from 125 to 20,825 km 2 . This variability was not due to size or sex but may be due to other intrinsic states for example reproductive condition or personality. The type of foraging (benthic vs. pelagic) varied from 56.6 ± 14.9% benthic dives in Prydz Bay through 42.1 ± 9.4% Terre Adélie to only 25.1 ± 8.7% in the Ross Sea reflecting regional hydrographic structure. The probability of benthic diving was less likely the deeper the ocean. Ocean topography was also influential at the population level; seals from Terre Adélie , with its relatively narrow continental shelf, had a core (50%) UD of only 200 km 2 , considerably smaller than the Ross Sea (1650 km 2 ) and Prydz Bay (1700 km 2 ). Sea ice concentration had little influence on the time the seals spent in shallow coastal waters, but in deeper offshore water they used areas of higher ice concentration. Marine Protected Areas (MPAs) in the Ross Sea encompass all the observed Weddell seal habitat, and future MPAs that include the Antarctic continental shelf are likely to effectively protect key Weddell seal habitat.

Dimethylsulfoniopropionate (DMSP) Increases Survival of Larval Sablefish, Anoplopoma fimbria - Jonathan S. F. Lee; Rachel S. Poretsky; Matthew A. Cook; Jose J. Reyes-Tomassini; Barry A. Berejikian; Frederick W. Goetz (Journal of Chemical Ecology, 2016)

Ontogenetic changes in embryonic and brain gene expression in progeny produced from migratory and resident O ncorhynchus mykiss - Garrett J. McKinney; Matthew C. Hale; Giles Goetz; Michael Gribskov; Frank P. Thrower; Krista M. Nichols (Molecular Ecology, 2015)
Little information has been gathered regarding the ontogenetic changes that contribute to differentiation between resident and migrant individuals, particularly before the onset of gross morphological and physiological changes in migratory individuals. The aim of this study was to evaluate gene expression during early development in Oncorhynchus mykiss populations with different life histories, in a tissue known to integrate environmental cues to regulate complex developmental processes and behaviours. We sampled offspring produced from migrant and resident parents, collecting whole embryos prior to the beginning of first feeding, and brain tissue at three additional time points over the first year of development. RNA sequencing for 32 individuals generated a reference transcriptome of 30 177 genes that passed count thresholds. Differential gene expression between migrant and resident offspring was observed for 1982 genes. The greatest number of differentially expressed genes occurred at 8 months of age, in the spring a full year before the obvious physiological transformation from stream‐dwelling parr to sea water‐adaptable smolts begins for migrant individuals. Sex and age exhibited considerable effects on differential gene expression between migrants and resident offspring. Differential gene expression was observed in genes previously associated with migration, but also in genes previously unassociated with early life history divergence. Pathway analysis revealed coordinated differential expression in genes related to phototransduction, which could modulate photoperiod responsiveness and variation in circadian rhythms. The role for early differentiation in light sensitivity and biological rhythms is particularly intriguing in understanding early brain processes involved in differentiation of migratory and resident life history types.

Matrix detachment and proteasomal inhibitors diminish Sulf-2 expression in breast cancer cell lines and mouse xenografts - Ashwani Khurana; Deok Jung-Beom; Xiaoping He; Sung-Hoon Kim; Robert C. Busby; Laura Lorenzon; Massimo Villa; Alfonso Baldi; Julian Molina; Matthew P. Goetz; Viji Shridhar (Clinical & Experimental Metastasis, 2013)

Lidar remote sensing variables predict breeding habitat of a Neotropical migrant bird - Scott J. Goetz; Daniel Steinberg; Matthew G. Betts; Richard T. Holmes; Patrick J. Doran; Ralph Dubayah; Michelle Hofton (Ecology, 2010)
A topic of recurring interest in ecological research is the degree to which vegetation structure influences the distribution and abundance of species. Here we test the applicability of remote sensing, particularly novel use of waveform lidar measurements, for quantifying the habitat heterogeneity of a contiguous northern hardwoods forest in the northeastern United States. We apply these results to predict the breeding habitat quality, an indicator of reproductive output of a well‐studied Neotropical migrant songbird, the Black‐throated Blue Warbler ( Dendroica caerulescens ). We found that using canopy vertical structure metrics provided unique information for models of habitat quality and spatial patterns of prevalence. An ensemble decision tree modeling approach (random forests) consistently identified lidar metrics describing the vertical distribution and complexity of canopy elements as important predictors of habitat use over multiple years. Although other aspects of habitat were important, including the seasonality of vegetation cover, the canopy structure variables provided unique and complementary information that systematically improved model predictions. We conclude that canopy structure metrics derived from waveform lidar, which will be available on future satellite missions, can advance multiple aspects of biodiversity research, and additional studies should be extended to other organisms and regions.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)